Analisis Komparatif Kemampuan Kecerdasan Buatan dalam Menganalisis Konten Media Sosial: Studi Kasus Grok (XAI), ChatGPT, dan Gemini - Herdian Nugroho, Bernardus (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study aims to compare the capabilities of three artificial intelligence (AI) platforms—Grok (XAI), ChatGPT (OpenAI), and Gemini (Google)—in analyzing social media content, specifically on Twitter (X). A descriptive qualitative method with a case study approach was employed. Three types of content—text, images, and videos—were used as test materials. Each AI platform was tasked with analyzing sentiment, context, and meaning embedded within the content. The results indicate that Grok excels in direct integration with Twitter, enabling real-time contextual reading of posts and interactions. In contrast, ChatGPT and Gemini demonstrated superior performance in in-depth analysis and multimodal interpretation when provided with explicit input. This study provides early insights into the comparative strengths and limitations of AI platforms for social media content analysis, offering practical recommendations for researchers and practitioners in selecting appropriate AI tools for digital public opinion analysis.